A Pilot Qualitative Case Study of Agricultural and Natural Resources Scientists’ Twitter Usage for Engaging Public Audiences - Jamie Loizzo; Catherine Jones; Abby Steffen (Journal of Applied Communications, 2019)
Scientists are frequently asked to broadly share their expertise and research with a variety of audiences, beyond typical academic circles in their home disciplines. That could include developing community engagement programs, school outreach, leveraging online social networks, and other activities. The purpose of this study was to examine U.S. agricultural and natural resources (ANR) scientists’ typical science communication channels, their experiences utilizing Twitter for sharing their knowledge, research, and engaging in online public science discussion. Diffusion of Innovations theory and the model of science in-reach versus outreach guided this study. Researchers used a qualitative case study design. Data collection included ANR scientist interviews (n = 8) and application of Internet-based research methods for observing scientists’ Twitter activities. Four themes emerged from the data: 1) academic journals and conferences as scientists’ typical communication channels, yet Extension efforts help to broaden audiences, 2) scientists expected research to be peer-reviewed before public dissemination to combat misinformation and spreading of ‘junk science’, 3) scientists balanced professionalism, personalization, promotion, and Twitter hashtags for engagement, and 4) scientist-identified barriers to using Twitter included lack of time and avoiding heated discussions. Recommendations include revisiting scientists’ job descriptions and expectations for online science engagement. Also, there should be continual development and implementation of science communication training for scientists targeting best Twitter practices, growing followers for outreach beyond academic colleagues and groups, using visuals for online engagement, intentional scheduling for social media, and how to effectively navigate heated online discussions.
Keywords: science communication; public science engagement; outreach; Twitter; diffusion of innovation; Internet-based research; qualitative